In vivo voltage-sensitive dye imaging of the insular cortex in nerve-injured rats. (10th November 2016) - Han, Jeongsoo; Cha, Myeounghoon; Kwon, Minjee; Hong, Seong-Karp; Bai, Sun Joon; Lee, Bae Hwan
Highlights: Excitability of the IC to peripheral stimulation is changed after nerve injury. Optical signals in the IC increased as the stimulation intensity was elevated. Plastic changes in the IC could be related to nerve injury-chronic pain. Abstract: The insular cortex (IC) is a pain-related brain region that receives various types of sensory input and processes the emotional aspects of pain. The present study was conducted to investigate spatiotemporal patterns related to neuroplastic changes in the IC after nerve injury using voltage-sensitive dye imaging. The tibial and sural nerves of rats were injured under pentobarbital anesthesia. To observe optical signals in the IC, rats were re-anesthetized with urethane 7 days after injury, and a craniectomy was performed to allow for optical imaging. Optical signals of the IC were elicited by peripheral electrical stimulation. Neuropathic rats showed a significantly higher optical intensity following 5.0 mA electrical stimulation compared to sham-injured rats. A larger area of activation was observed by 1.25 and 2.5 mA electrical stimulation compared to sham-injured rats. The activated areas tended to be larger, and the peak amplitudes of optical signals increased with increasing stimulation intensity in both groups. These results suggest that the elevated responsiveness of the IC to peripheral stimulation is related to neuropathic pain, and that neuroplastic changes are likely to be involved in the IC after nerve injury.